2016
DOI: 10.1152/ajpheart.00159.2016
|View full text |Cite
|
Sign up to set email alerts
|

Ventricular stimulus site influences dynamic dispersion of repolarization in the intact human heart

Abstract: Spatial variation of restitution in relation to varying stimulus site is poorly defined in the intact human heart. Repolarization gradients were shown to be dependent on site of activation with epicardial stimulation promoting significant transmural gradients. Steep restitution slopes were predominant in the normal ventricle.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
30
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1
1

Relationship

6
2

Authors

Journals

citations
Cited by 22 publications
(35 citation statements)
references
References 62 publications
5
30
0
Order By: Relevance
“…Based on previous studies reporting that the T‐wave morphology reflects the spatio‐temporal dispersion of repolarization, and that dispersion of repolarization changes with heart rate, we hypothesized that the morphology of the T‐wave would vary when measured at different heart rate values. TMR may therefore be in some way related to the spatial heterogeneity of APD restitution.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on previous studies reporting that the T‐wave morphology reflects the spatio‐temporal dispersion of repolarization, and that dispersion of repolarization changes with heart rate, we hypothesized that the morphology of the T‐wave would vary when measured at different heart rate values. TMR may therefore be in some way related to the spatial heterogeneity of APD restitution.…”
Section: Discussionmentioning
confidence: 99%
“…The restitution of ventricular repolarization reflects the adaptation of repolarization to changes in heart rate, with the slope of the repolarization restitution indicating the variation of the action potential duration (APD) per RR increment . Heterogeneity in the restitution properties across the ventricle has been reported to contribute to the establishment of repolarization dispersion gradients, which, when accentuated, are associated with greater propensity to suffer from malignant ventricular arrhythmia . Evaluation of the dispersion in repolarization restitution is commonly performed from invasive procedures, which limit its use for risk assessment.…”
Section: Introductionmentioning
confidence: 99%
“…The non-contact mapping data consisting of 256 unipolar electrograms were collected with a recording bandwidth of 0-300 Hz in all cases and measurements made with a filter band width of 0.1-25 Hz. Electrograms were exported and analysed using semi-automated custom software running in Matlab (The Mathworks Inc., MA, USA) (10,11). During pacing, the time from pacing artefact to the steepest negative deflection (dV/dt min ) was used as the local activation time (AT).…”
Section: Offline Analysesmentioning
confidence: 99%
“…We paced from the RV apex; however, it is known that if the pacing site is changed, this may shift activation and repolarisation (11) and may in some cases shift exit sites for VT. Simulations in ischaemic cardiomyopathy have demonstrated that the RVI map may also change (7) and criteria for the selection of optimal pacing site should be identified in further studies. Our study population was relatively small, and to enable clinical translation, prospective testing in a larger cohort would be necessary to enable clinical translation and demonstrate its superiority over other common substrate mapping procedures.…”
Section: Limitationsmentioning
confidence: 99%
“…During an electrophysiological study for supraventricular tachycardia in a patient with structurally normal ventricles, two decapolar catheters were placed in the left and right ventricles. Unipolar electrograms were referenced against the WCT, sampled at 2 KHz and recorded with amplifier with bandwidth 0.05-500 Hz as in previous studies [9]. Ventricular pacing was established from the RV apex.…”
Section: Experimental Datamentioning
confidence: 99%